The both sides of using WebQuesttechnology in increasing of Speaking Skill at school (Eurasian Journal of Learning and Academic Teaching, 2022)
The work touched the new strategies in teaching foreign languages, exactly the WebQuest technology. In our time apart from receiving knowledge of foreign languages than first language, has become highly profitable. In the contemporary educational process teachers can use new technologies and forms of interaction with students and they are based on the intensification of independent activities and the straight participation of students in the educational process. WebQuest-technology is a new type of an educational organization, but it has some negatives along with the positives in growth of the learners’ active participation during the clue of the given problems in the search tasks.